The Ineffectiveness of UNHCR in Handling the Myanmar Conflict - Sabil, Akbar Averroes; Surwandono, Surwandono (Nation State: Journal of International Studies, 2023)
UNHCR has a history of success in managing humanitarian issues and ultimately contributing to the birth of a new consciousness to consciously end conflicts. However, in the context of the conflict in Myanmar, UNHCR, which has systematically conducted humanitarian interventions to build a new consciousness to end the conflict, has failed to manage the humanitarian interventions to build a new consciousness to end the conflict. This article will explain the factors of failure in ending the conflict in order to see how deep the value of peace consciousness of peace consciousness can influence decisions in the conflict. This article finds that the Myanmar government's lack of political awareness of a number of ratified humanitarian conventions has made UNHCR's humanitarian interventions hit and run, so that peace values do not grow into core values. UNHCR's failure to transform the Refugee Convention into a new value in the ASEAN normative structure has rendered double contingency ineffective.